Pengaruh aplikasi terra preta terhadap kandungan protein jagung hibrida: Eksperimen acak kelompok - Ilmiyati, Liyana; Relawati, Rikeu (Poltekkes Kemenkes Aceh, 2025)
Background: The high protein content in hybrid corn is needed by the body to support health, so the quality of production must be carefully maintained. Terra preta is a type of fertile soil that can enhance nutrient retention through biochar, thereby improving agricultural production both in terms of quality and sustainable quantity.Objective: To analyze the potential use of Terra Preta in increasing the protein content of hybrid corn.Methods: The research was conducted from September to December 2023. This study used a Randomized Block Design (RBD) method with 2 treatment levels (0 tons/ha and 15 tons/ha of terra preta). Each treatment was replicated 3 times, resulting in 12 experimental plots. Corn planting was carried out in Tolengas Village, Sumedang, and protein content testing was conducted at the UPTD Testing and Application of Product Quality (PPMPP) of the Fisheries and Marine Office, Cirebon City, West Java Province.Results: Hybrid corn treated with terra preta showed better growth in terms of plant height, stem diameter, and number of leaves compared to corn without terra preta. There was a significant difference in the protein content analysis of hybrid corn (p = 0,01, 95% CI = 7,322–11,001). The protein content of hybrid corn seeds treated with 0 tons/ha of terra preta (9,31%) was higher than that treated with 15 tons/ha of terra preta (9,02%). Conclusion: The highest protein content was observed in the 0 tons/ha treatment (9,31%). Terra preta benefits plant growth but does not contribute to increased protein content.